2010
DOI: 10.1001/archgenpsychiatry.2010.99
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Intellect and Memory

Abstract: Using the largest international familial schizophrenia cohort to date, we showed that a substantial portion of the phenotypic correlation between schizophrenia and cognition is caused by shared genetic effects. However, because the phenotypic and genetic correlations are far from unity, the genetics of schizophrenia are clearly not merely the genetics of cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
38
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(48 citation statements)
references
References 37 publications
7
38
0
Order By: Relevance
“…The present finding of a link between intellectual function and variation in the NMDA-RC therefore supports a genetic link between schizophrenia and intelligence, in keeping with behaviour genetic 42 research, and also with recent polygenic risk studies of a sub-set of the present cohorts that indicated an overlap of polygenic risk factors for schizophrenia and for cognitive ageing. 84 The genetic link between schizophrenia and cognitive abilities appears to be region rather than variant specific.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present finding of a link between intellectual function and variation in the NMDA-RC therefore supports a genetic link between schizophrenia and intelligence, in keeping with behaviour genetic 42 research, and also with recent polygenic risk studies of a sub-set of the present cohorts that indicated an overlap of polygenic risk factors for schizophrenia and for cognitive ageing. 84 The genetic link between schizophrenia and cognitive abilities appears to be region rather than variant specific.…”
Section: Discussionsupporting
confidence: 90%
“…40 De novo mutations in the ARC protein have been implicated in schizophrenia, 20 a disease in part predicted by a low premorbid cognitive ability, 41 which may be due to a shared genetic component between the two traits. 42 …”
Section: Introductionmentioning
confidence: 99%
“…28, 29, 30 However, as we learn more about the polygenic architecture of intelligence and mental disorders, single-nucleotide length polymorphism (SNP)-based bivariate analyses may provide more robust estimates of the shared genetic contribution of common genetic variants. 31, 32, 33 Indeed, a recent study reported that (a) polygenic SNP scores derived to predict increased cognitive ability were associated with a reduced risk of schizophrenia, and conversely that (b) polygenic SNP scores derived to predict increased risk of schizophrenia were associated with lower scores on cognitive ability.…”
Section: Discussionmentioning
confidence: 99%
“…Family studies show that the offspring of parents with schizophrenia have worse cognitive function than the offspring of unaffected parents [31], and that cognitive impairment is associated with familial risk of schizophrenia [32]. Applying genetic modeling to a combined family and twin sample, Toulopoulou and colleagues [33] showed that a large proportion of the phenotypic correlations between schizophrenia and cognition are due to shared genetic effects.…”
Section: Family Studiesmentioning
confidence: 99%